WAYS TO ENSURE THE ECONOMIC DEVELOPMENT OF THE COUNTRY THROUGH THE DEVELOPMENT OF THE CAPITAL MARKET (Intent Research Scientific Journal, 2023)
The article examines the specific features of the stock market, its relationship with the country's economic growth indicators, analyzes several years' indicators of the state of the stock market in the Republic of Uzbekistan, the operation of the stock market recommendations aimed at improving the mechanisms have been developed.